Plasmalogen synthesis is regulated via alkyl-dihydroxyacetonephosphate-synthase by amyloid precursor protein processing and is affected in Alzheimer’s disease - Grimm, Marcus Otto Walter; Kuchenbecker, Johanna; Rothhaar, Tatjana L.; Grösgen, Sven; Hundsdörfer, Benjamin; Burg, Verena K.; Friess, Petra; Müller, Ulrike C.; Grimm, Heike S.; Riemenschneider, Mathias; Hartmann, Tobias (Journal of neurochemistry, 2011)
J. Neurochem. (2011) 116, 916-925. Abstract Lipids play an important role as risk or protective factors in Alzheimer’s disease, which is characterized by amyloid plaques composed of aggregated amyloid-beta. Plasmalogens are major brain lipids and controversially discussed to be altered in Alzheimer’s disease (AD) and whether changes in plasmalogens are cause or consequence of AD pathology. Here, we reveal a new physiological function of the amyloid precursor protein (APP) in plasmalogen metabolism. The APP intracellular domain was found in vivo and in vitro to increase the expression of the alkyl-dihydroxyacetonephosphate-synthase (AGPS), a rate limiting enzyme in plasmalogen synthesis. Alterations in APP dependent changes of AGPS expression result in reduced protein and plasmalogen levels. Under the pathological situation of AD, increased amyloid-beta level lead to increased reactive oxidative species production, reduced AGPS protein and plasmalogen level. Accordingly, phosphatidylethanol plasmalogen was decreased in the frontal cortex of AD compared to age matched controls. Our findings elucidate that plasmalogens are decreased as a consequence of AD and regulated by APP processing under physiological conditions.
Gesehen am 11.07.2022